Dead laws for dead men : the politics of federal coal mine health and safety legislation - Curran, Daniel J. (Pitt series in social and labor history., 1993)
The coal mining industry has claimed the lives of more than 100,000 miners since the turn of the century and has disabled hundreds of thousands more. This account of the struggle for coal mine health and safety legislation in the United States examines the series of laws that steadily expanded the role of the federal government from the late 1800s through the 1980s. After reviewing the historical evidence, Daniel J. Curran concludes that federal legislation has done little to change the conditions in the coal mines. Moreover, the existence of laws did not even guarantee that the established standards could be implemented and enforced in a way that would resolve health and safety problems. By reconstructing the socioeconomic environment surrounding the creation of each major federal coal mine safety act, Curran argues that legislation remains open to interpretation throughout the time it is in effect. His analysis of enforcement during the 1980s in particular illustrates how dramatically the mission of an agency can be altered as economic conditions and political agendas change. Curran examines the Federal Coal Mine Health and Safety Act of 1969, discussing the economic and political milieu surrounding the evolution of the act, the interest groups involved, the central issues debated, and the final version of the law. He then evaluates the implementation and enforcement of the statutes in the law, utilizing statistical data on enforcement and assessment from 1970 to 1977. In exploring the impact of the Federal Mine Safety and Health Amendments Act of 1977, Curran reviews revisions in the law from 1978 to 1988. While coal production expanded in the 1980s, the demand for workers declined, and the Reagan administration's antilabor orientation and deregulatory stance worked against the enactment of new health and safety legislation. Even though disasters occurred, the fatality rate fluctuated significantly, and the injury rate rose dramatically, no new laws were enacted because the social conditions necessary to bring the problem of health and safety to the forefront did not exist. Consequently, the harsh reality of the coalfields remained.